Influence of Leadership Style, Career Development, and Work Satisfaction on Employee Performance In Tropical Disease Institutions of Airlangga University Surabaya - Mahendra Fredyantono Rahadytya; Hermien Tridayanti (Yayasan Ahmar Cendekia Indonesia, 2020)
This study aims to determine and analyze the Leadership Style, Career Development, and Job Satisfaction simultaneously and significantly to Employee Performance. This research is qualitative research. The population and sample based on the distribution of questionnaires to employees of the Surabaya Tropical Disease Institute were taken as many as 59 respondents. Data collection techniques using interviews, observation, and questionnaires. Analysis of the data used is the reliability test, validity test, classic assumption test, and multiple linear analysis test. The results of the study simultaneously and partially Leadership Style, Career Development, and Job Satisfaction have a positive and significant effect on employee performance. The F test result is 16.703 greater than the 2.00 table simultaneously. Partially the Leadership Style obtained a significant value of 0,000 (less than 0.05) significant effect on employee performance, Career Development obtained a significant value of 0.025 (less than 0.05) significant effect on employee performance, and Job Satisfaction obtained significant value of 0.049 (less than 0.05) has a significant effect on employee performance.